The Effects of 830nm Light on Inflammation in Retinitis Pigmentosa - (:unkn) unknown (My University, 2015)
Purpose: Retinitis Pigmentosa (RP) is an inherited retinal degenerative disease and the most common cause of blindness in developed countries, affecting approximately 1 in 4,000 people. RP is characterized by photoreceptor cell death and recent studies suggest that chronic inflammation may play a key role in the pathogenesis of RP. Currently, there are no known treatments or preventive measures to delay or halt the loss of photoreceptor cells. Photobiomodulation (PBM) by light in the far-red or near-infrared (NIR) range of the light spectrum has been documented to help promote cell survival and reduce inflammation in several disease states. Recent studies in the P23H rat model of RP have shown that 830nm PBM attenuated photoreceptor cell loss and protected retinal function. The current studies test the hypothesis that 830nm PBM produces an anti-inflammatory environment in the retina to protect against photoreceptor cell loss. Methods: Studies were conducted in compliance with the ARVO Statement for the Use of Animals in Ophthalmic and Visual Research. P23H rats were irradiated with 830nm light (180 s; 25 mW/cm2; 4.5 J/cm2) using a light-emitting diode array once per day from postnatal day (p)17 to 27. Sham treated controls were restrained for 180 seconds, but not exposed to the 830nm light. Retinas were harvested at p30. Retinal concentrations of ten inflammatory mediators were determined using a multiplex bead-based immunosorbent assay. Results: Our findings indicate that retinal concentrations of four of the ten inflammatory mediators, CINC-3, IL-10, VEGF, and TIMP-1 differed between the dystrophic P23H rats and the non-dystrophic SD rats. Statistically significant differences were only observed in TIMP-1, with concentrations in the P23H retinas that were twice that measured in the SD retinas. 830nm PBM produced no changes in retinal concentrations of the 10 inflammatory mediators measured compared to the sham treatment. Conclusion: Our data indicated that the inflammatory environment of the dystrophic P23H rat and the non-dystrophic SD rat differ. The data also shows that 830nm PBM had no measurable effect on these inflammatory mediators at p30. Further studies with greater numbers of animals are needed to investigate the time course of inflammation in this rodent model of RP and to define potential effects of PBM.
Keywords: Immunology; Inflammation; Photobiomodulation; Retina; Retinal Degeneration